2002
DOI: 10.1046/j.1365-2796.2002.00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards clinical research amongst participants and nonparticipants

Abstract: Results. Altruistic motives of physicians to conduct medical research were highly rated. Attitudes towards clinical research were positive in all groups, with nonparticipant respondents being the least positive. Eight to nine tenths found scienti®c testing necessary before general health service implementation. Trial participants were, as compared with nonparticipating respondents, more positive towards both participation of self and others. Both personal and altruistic motives for participation were highly ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 37 publications
7
113
2
Order By: Relevance
“…Consent to be interviewed was obtained from patients who agreed to participate in a questionnaire-study exploring attitudes towards and experiences with clinical trials [18]. The survey fulfilled the demands of Danish law and the Helsinki Declaration IV, and was approved by the relevant regional Research Ethics Committees (reg.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consent to be interviewed was obtained from patients who agreed to participate in a questionnaire-study exploring attitudes towards and experiences with clinical trials [18]. The survey fulfilled the demands of Danish law and the Helsinki Declaration IV, and was approved by the relevant regional Research Ethics Committees (reg.…”
Section: Methodsmentioning
confidence: 99%
“…All patients found eligible to participate in the clinical cancer trials were also eligible to participate in a questionnaire study, and only six of the approached patients in our full complex of questionnaire-studies declined to participate [17,18]. Patients accepting to complete questionnaires were asked whether we could contact them at the end of the treatment to set up an interview.…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…If the willingness to participate in clinical research is defined as an illness coping behaviour weighted by patients own beliefs for and against the trial, the conclusion might be that patients are quite predictable in their decision to take part in research, as observed by Verheggen at al., 1998 (12). However, there is a recognised variety of psychological factors involved in every individual decision related to participation in clinical research activities, such as: personal benefits from participation in a trial, altruistic and non-altruistic motives, what do patients perceive as disadvantages of clinical research and effects of the trial medication, and previous experience of clinical research (13,14).…”
Section: Discussionmentioning
confidence: 99%